Optimization of Health Risk Assessment Through the Similar Exposure Group (SEG) Approach in Mining Occupational Health Management - Amrulloh, Muhammad Osaegi Restu; Agus, Mohammad Aulia Arif; Humam, Muhamad Sayyid; Aris, Trio (BKM Public Health and Community Medicine, 2024)
Purpose: The Similar Exposure Group (SEG) approach has become an important strategy in optimizing Health Risk Assessment (HRA) in mining work environments. With a focus on managing employee health risks, this research identifies appropriate SEGs in the context of application to mining work environments, carefully evaluates exposures and assesses health risks in detail. Content: Through desk study, literature analysis, and field observations, the SEG approach was scrutinized to improve its understanding and practical application in HRA. This study aims to determine the extent to which the integration of SEG in the HRA process can improve the effectiveness of health risk management in the work environment of PT Putra Perkasa Abadi. The comprehensive application of SEG was shown to help identify and manage health risks more efficiently, providing a solid foundation for designing more effective prevention strategies. The conclusion of this study highlights the importance of the SEG approach in HRA as a step towards a better understanding of managing the work environment at PT Putra Perkasa Abadi in improving employee health risk prevention efforts.